Hydraulics in civil and environmental engineering - Chadwick, A.J. (Andrew John) (E & FN Spon, 1993)
The authors have incorporated the results of many of the recent advances in research and development which are currently finding their way into engineering practice. They have taken full advantage of the widespread availability of the computer in the presentation of computational modelling techniques and their application. The text incorporates a comprehensive set of worked examples to illustrate the uses of the theory, and problems and computer programs are appended. Part 1 introduces the theoretical concepts essential to hydraulic engineering. Hydrostatics, hydro-dynamics and flow in pipes and channels are all treated thoroughly. The authors then proceed to cover hydrology, sediment transport, wave theory, river and coastal engineering and water quality modelling. This provides a broad, holistic view of the subject, enabling the reader to envisage the complexity of real problems, and the design philosophies required for their solution.